Turkish Foreign Policy in an Age of Uncertainty - Larrabee, F. Stephen (RAND Corporation, 2003)
The authors describe the challenges and opportunities facing Turkey in the international environment during a time of extraordinary flux. Special emphasis is given to the strategic and security issues facing Turkey, including a number of new issues posed by the terrorist attacks of September 2001 and the subsequent international response. They conclude by offering some prognostications regarding the country's future and their implications on Turkey's western partners.